Answer:
5(d - 2) = 45
Step-by-step explanation:
Solve the given equation for d
3(d + 1) = 4(d - 2) ← distribute parenthesis on both sides
3d + 3 = 4d - 8 ( subtract 3d from both sides )
3 = d - 8 ( add 8 to both sides )
11 = d
Then
5(d - 2) = 5(11 - 2) = 5(9) = 45
Answer:
In number 1:
m = 10/3
b = 19
Step-by-step explanation:
To find the answers to these, simply look to the coefficient of x and the constant at the end of the equation. The number attached to x is always m (which is known as the slope). The number at the end is b (or the y-intercept).
The correct answer would be:
-5
-4
-3
-2
-1
0
1
2
3
4
5
Answer:
16
Step-by-step explanation: